The impact of agricultural financing on achieving agricultural output The Agricultural Cooperative Bank in Iraq as a case study during the period (1998-2014) - Ismail Aziz Assad (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
The Agriculture sector plays an important role to achieve economic development for any country whether advance country or underdeveloped country , that Agriculture activity consider important economic activity and basic source to cover the nutritional needs for population , also Agriculture consider source of income and wealth , its contribute to reduce unemployment .the Agriculture bank provides credit facilities for deferent periods in order to activate the Agriculture activity and perform .this role lying on agriculture cooperative bank is big due to the need of the agriculture sector to the capital in order to providing infrastructure to this sector.